FUNGSI DAN FAKTOR PENYEBAB PENGGUNAAN KODE TUTUR KELUARGA MUDA DI KABUPATEN SELUMA (KAJIAN SOSIOLINGUISTIK) - Yeyen Puspita Sari; Kasmantoni Kasmantoni; Ixsir Eliya (Universitas Negeri Padang, 2021)
The speech code that varies in Seluma Regency is very varied because there are young families or people who come from different ethnic groups. This study aims to describe the functions and factors behind the use of various codes in young families in Padang Rambun Village, Seluma Regency. The type of research in this study is to use a theoretical and methodological approach. The method used in this research is descriptive qualitative research method. The theoretical approach used is a sociolinguistic approach, namely an approach that relates to the theory or science of language use with the community in this study the science of language use in young family communities in Padang Rambun Village. While the methodological approach is a qualitative descriptive approach. Based on the results of the study, it was concluded that there were six functions in the speech acts of young families, namely emotive, conative, referential, poetic, fatic, and metalingual functions. The factors behind the occurrence of various codes in the speech acts of young families in Padang Rambun Village, Seluma Regency, there are two factors, namely, the occurrence of transmigration and the number of young families.Kata Kunci: Ragam Kode, Tindak Tutur, Keluarga Muda, Kelurahan Padang Rambun.